Pengaruh Substitusi Santan dengan Susu Biji Labu terhadap Karakteristik Rendang Daging Sapi: - Heri Atmojo; Muhammad Faiq Setiaputra (JURNAL PARIWISATA VOKASI, 2026)
This study aimed to determine the effect of substituting coconut milk with pumpkin seed milk on the flavor, nutritional value, and production cost of beef rendang. The method used was an experiment involving evaluations by professional and non-professional panelists of color, aroma, taste, and texture. The results showed that rendang made with pumpkin seed milk had a very high acceptance rate and was able to compete with the control rendang. Overall, the experimental product received an average score of 4.31, while the control rendang scored 4.29. From a nutritional perspective, the experimental rendang had lower calorie and fat content—2,846.43 kcal and 191.58 grams, respectively—compared to the control rendang, which contained 4,666.43 kcal and 387.86 grams. However, its production cost was higher, at Rp11,456 per serving. These results indicate that pumpkin seed milk has the potential to serve as a healthier alternative to coconut milk in rendang preparation. Keywords: beef rendang, pumpkin seed milk, coconut milk substitute, nutritional value, flavor, food costs.